The Malaise of Compulsory Conciliation: Strike Prevention in Canada during World War II - Webber, Jeremy (Labour / Le Travail, 1985)
During World War II, the government of Canada sought to prevent strikes primarily through the use of "compulsory conciliation:" in specified industries, strikes and lockouts were prohibited until a government-sponsored board had investigated the dispute and delivered its report. This paper examines the operation of that regime during the war years. It highlights the tension between two alternative views of the boards' function (adjudication and mediation), indicates how the government manipulated the conciliation process in order to prevent or delay strikes, discusses briefly the reasons invoked by boards in their judgements, and demonstrates the frustration arising from the government's reluctance to prescribe clear norms of industrial conduct. In the turbulent wartime economy, compulsory conciliation failed to achieve the level of industrial peace demanded of it. Eventually, mandatory wage controls and a labour code modeled on the American Wagner Act were adopted, restricting the scope of the conciliation regime.
Keywords: CONCILIATION (Civil procedure); Canada; DEMONSTRATIONS (Collective behavior); DIRECT action; Labor disputes; Research; STRIKES & lockouts; WORLD War, 1939-1945